2001
DOI: 10.7326/0003-4819-135-11-200112040-00007
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Virologic and Clinical Outcomes in HIV-1–Infected Patients Receiving Concurrent Treatment with Indinavir, Zidovudine, and Lamivudine: AIDS Clinical Trials Group Protocol 320

Abstract: The HIV-1 RNA level and CD4 cell count achieved at 8 weeks of treatment are important predictors of subsequent virologic and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…ACTG 320 was a phase III trial of subjects with Ͼ3 months of prior experience with zidovudine and CD4 cell counts of Յ200 cells/mm 3 , and it demonstrated that treatment with the combination of indinavir, zidovudine, and lamivudine (indinavir arm) was superior to treatment with zidovudine and lamivudine (dual-nucleoside arm) in delaying clinical progression (9). A total of 1,178 subjects had been randomized by 21 February 1997, the date that the study was terminated and the subjects were unblinded, following an interim review that demonstrated an improved clinical outcome in the indinavir arm of the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ACTG 320 was a phase III trial of subjects with Ͼ3 months of prior experience with zidovudine and CD4 cell counts of Յ200 cells/mm 3 , and it demonstrated that treatment with the combination of indinavir, zidovudine, and lamivudine (indinavir arm) was superior to treatment with zidovudine and lamivudine (dual-nucleoside arm) in delaying clinical progression (9). A total of 1,178 subjects had been randomized by 21 February 1997, the date that the study was terminated and the subjects were unblinded, following an interim review that demonstrated an improved clinical outcome in the indinavir arm of the study.…”
Section: Methodsmentioning
confidence: 99%
“…If either of these measurements was outside the assay's range of quantification, then an imputed value was used: if a value of Ͻ500 copies/ml was obtained (which occurred in 1% of subjects), then a value of 500 copies was used, and if a value of Ͼ750,000 copies/ml was obtained (which occurred in 9% of subjects), then a value of 750,000 copies was used. The baseline CD4 cell count was defined as the mean of the preentry and entry measurements and excluded the screening value, which had to be Յ200 cells/mm 3 . Analyses were based on subjects with available data, regardless of whether they discontinued their randomized treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each case, there were 1) viral genotype and/or phenotype findings that indicated viral sensitivity to the patient's medication regimen, 2) evidence of treatment failure, as indicated by HIV-1 RNA levels of Ͼ4 log 10 copies per mL in 2 consecutive laboratory evaluations, and 3) caregiver insistence that medications were being administered regularly. The criterion and threshold for increased viral loads of Ͼ4 log 10 HIV RNA copies per mL were chosen because of 1) robust evidence in the medical literature that HAART results in an expected decrease in the viral load with time, with a decrease to Ͻ5000 (3.7 log 10 ) HIV RNA copies per mL being expected after 4 to 8 weeks of therapy 20,21 and 2) the 2002 recommendations for HAART for asymptomatic patients with viral loads of Ͼ4.7 log 10 HIV RNA copies per mL, regardless of the CD4 ϩ T cell counts. 22 All of our patients received HAART (Ն2 nucleoside analog reverse transcriptase inhibitors and Ն1 protease inhibitor or nonnucleoside reverse transcriptase inhibitor) since its availability.…”
Section: Subjectsmentioning
confidence: 99%
“…The most mature and well-established markers of disease progression are CD4 T-helper cell count and RNA copy number (2,3,5,7). While these parameters are straightforwardly used for cross-sectional classification of patients with respect to clinical state, much uncertainty exists regarding evaluation and interpretation of changes in these markers over time (4).…”
mentioning
confidence: 99%